The double burden of overnutrition and undernutrition in mother−child dyads in Kenya: demographic and health survey data, 2014 - Peninah Kinya Masibo; Felix Humwa; Teresia Njoki Macharia (Journal of Nutritional Science, 2020)
The double burden of overnutrition and undernutrition is rapidly becoming a public health concern in low- and middle-income countries. We explored the occurrence of mother−child pairs of over- and undernutrition and the contributing factors using the 2014 Kenya Demographic and Health Survey data. A weighted sample of 7830 mother−child pairs was analysed. The children's nutritional status was determined using the WHO 2006 reference standards while maternal nutritional status was determined with BMI. Descriptive statistics, bivariate and multivariate logistic regression analysis were conducted. The proportion of overweight and obese mothers was 26 % (18·8 % overweight and 7·2 % obese). The prevalence of child stunting, underweight and wasting was 26·3, 12·8 and 5·1 %, respectively. Out of the overweight/obese mothers (weighted n 2034), 20 % had stunted children, 5·4 % underweight children and 3·1 % wasted children. Overweight/obese mother−stunted child pairs and overweight/obese mother−underweight child pairs were less likely to occur in the rural areas (adjusted OR (aOR) = 0·43; P < 0·01) in comparison with those residing in the urban areas (aOR = 0·54; P = 0·01). Children aged more than 6 months were more likely to be in the double burden dyads compared with children below 6 months of age (P < 0·01). The double burden mother−child dyads were more likely to be observed in wealthier households. Mother−child double burden is a notable public health problem in Kenya. Household wealth and urban residence are determinants of the double burden. There is need for target-specific interventions to simultaneously address child undernutrition and maternal overweight/obesity.